2009
DOI: 10.1007/s12648-009-0122-z
|View full text |Cite
|
Sign up to set email alerts
|

Solitons of the KP equation in dusty plasma with variable dust charge and two temperature ions: energy and stability

Abstract: The propagation of nonlinear waves in dusty plasmas with variable dust charge and two temperature ions is analyzed. By using the reductive perturbation theory, the Kadomtsev-Petviashivili (KP) equation is derived. A Sagdeev potential has been investigated. This potential is used to study the stability conditions for existence of solitonic solutions. Also, it is shown that a rarefactive soliton can exist in most of the cases. The energy of the soliton has been calculated and by using the standard normal-mode an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Kaur et al [22] investigated solitary features in the framework of the Kortweg-deVries (KdV) equation obtained from a plasma with nonthermal electrons and weakly relativistic ions using the RPT. Similarly, other authors have studied different dynamical features in different plasma models under the framework of the KdV equation [23], modified KdV equation [24], modified Gardner equation [25], Burgers equation [26], nonlinear Schrödinger equation [27], Kadomtsev-Petviashivili [28] obtained using the RPT. Poria and Ghosh [29] studied a magnetized electron-ion plasma with Boltzmann distributed electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Kaur et al [22] investigated solitary features in the framework of the Kortweg-deVries (KdV) equation obtained from a plasma with nonthermal electrons and weakly relativistic ions using the RPT. Similarly, other authors have studied different dynamical features in different plasma models under the framework of the KdV equation [23], modified KdV equation [24], modified Gardner equation [25], Burgers equation [26], nonlinear Schrödinger equation [27], Kadomtsev-Petviashivili [28] obtained using the RPT. Poria and Ghosh [29] studied a magnetized electron-ion plasma with Boltzmann distributed electrons.…”
Section: Introductionmentioning
confidence: 99%
“…The non-linear behavior of electrostatic waves in a plasma with this trapped state [25−27] has received considerable attention and been studied by a number of au-thors in the last few years in unmagnetized and magnetized plasmas [26−29] . Most of the studies have focused on the derivation of K-dV and K-P equations using the reductive perturbation technique [30,31] as well as the Sagdeev potential approach [32] . For example, Mamun et al [24] investigated the effects of vortex-like and non-thermal ion distributions within the small amplitude regime using a modified K-dV equation, and they concluded that there exists the possibility of coexistence of large amplitude rarefactive as well as compressive DASWs, whereas these structures appear independently when the wave amplitudes become infinitely small [29] .…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear propagation of sound waves in plasmas has been studied over last few years [1][2][3][4][5][6][7][8][9][10][11][12]. Quantum effect on plasma has to be considered when the de Broglie wavelength of the charge carriers is comparable with the dimension of the system.…”
Section: Introductionmentioning
confidence: 99%